Authenticity control of pine sylvestris essential oil by chiral gas chromatographic analysis of α-pinene - Martina Allenspach (Nature Portfolio, 2021)
Abstract Numerous terpenes present in essential oils (EOs) display one or more chiral centers. Within the same genus the enantiomeric ratio of these compounds can be different. Thus, the determination of enantiomers is a valuable tool to evaluate authenticity and quality of EOs. In here, the terpene profile of primary and commercial pine EOs was analyzed by conventional and chiral gas chromatography coupled to a flame ionization detector. The enantiomeric excess of ( ±)-α-pinene was determined and significant differences between primary and commercially available EOs were observed. Primary EOs of Pinus sylvestris L. showed a positive enantiomeric excess of (+)-α-pinene whereas commercial EOs labeled as P. sylvestris L. exhibited an enantiomeric excess of (−)-α-pinene. Thus, chiral analysis provides useful information on the authenticity of pine EOs and allows to uncover possible mislabeling, the use of the wrong herbal substance and sources of adulteration in pine oil.